Computational Science in the educational curriculum - Cabrera Delgado, José Manuel (Avances en Supervisión Educativa, 2017)
How to incorporate Computer Science (CS) into the basic education curriculum continues to be subject of controversy at the European level. Without there being a defined strategy on behalf of the European Union in this respect, several countries have begun their incorporation showing us the advantages and difficulties of such action. Main elements of CS, such as computational thinking and coding, are already being taught in schools, establishing the need for a curriculum adapted to the ages of the students, training for teachers and enough resources. The purpose of this article, from the knowledge of the experience of these countries, is to respond, or at least to reflect, on the answers to the following questions: what is CS?, what are their main elements?, why is it necessary?, at what age should CS be taught?, what requirements are needed for their incorporation?